Contested Puberty: Judicial Discretion, Moral Regulation, and the Persistence of Child Marriage in Indonesia - Y Sonafist; Azhar; Syukrawati; Nurjanah Nurjanah; Wail Abouabaid (Nusantara: Journal of Law Studies, 2026)
The 2019 revision of Indonesia's Marriage Law raised the minimum marriage age to 19, yet produced a striking paradox: rather than reducing child marriage, it precipitated a sharp increase in marriage dispensation applications in religious courts. This article argues that the reform displaced the site of legitimation for child marriage—shifting authorization from administrative registration to judicial approval through dispensation mechanisms—revealing not merely a failure of legal implementation, but a deeper process through which the state and judiciary actively reproduce the legal boundaries of adulthood and child protection. Drawing on a socio-legal framework, this study employs critical discourse analysis of two complementary sites: the normative constructions embedded in the Marriage Law—particularly the ambiguous phrase "urgent reasons"—and the judicial reasoning inscribed in religious court dispensation decisions. An empirical examination of trends in national post-reform dispensation supplements this dual-object analysis. Together, these methods trace a discursive struggle between two competing normative orders: state-led discourses of child protection and gender equality on one side, and moral-religious discourses mobilized by judges in interpreting puberty, social readiness, and family honor on the other. The findings reveal that broad judicial discretion functions as an institutional mechanism through which child marriage continues to obtain legal legitimacy despite the formally elevated minimum age, which this article terms the "judicial backdoor." Judges routinely authorize dispensations by invoking moral-religious considerations such as pregnancy, the imperative to prevent zina, and avoidance of social stigma, thereby subordinating child rights protections to communal moral norms. Without standardized criteria for "compelling grounds" and a child rights-based evaluative framework, legal reform risks functioning as a symbolic gesture that leaves the patriarchal structures underpinning child marriage substantively intact. This article contributes to broader debates on legal pluralism, judicial discretion, and the challenges of implementing gender-sensitive reform in socio-religious contexts.